2013
DOI: 10.1021/bm400323c
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of Water-Insoluble Drugs Due to Random Amphiphilic and Degradable Poly(dimethylmalic acid) Derivatives

Abstract: Amphotericin B (AmB) and clofazimine are potent drugs hindered by their low water solubilities and their toxicities. Carriers able to increase their apparent water solubilities are needed for these drugs and for other molecules with similar properties. Random amphiphilic copolymers derived from poly(dimethylmalic acid) were obtained using different hydrophobization ratios and side group sizes. Apparent water solubilities of pyrene, clofazimine, and AmB were increased up to 10 000, 20 000 and 1000 times, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…It was reported that the solubility of protonated CFZ under acidic conditions is 20 mg L −1 . 25 The phase solubility data based on the HPLC-UV method and 1 H NMR titration method afforded the binding constant K a of 2.66 (±0.13) × 10 4 M −1 and 3.15 (±0.16) × 10 5 M −1 , respectively. HPLC analysis is often considered as a more accurate quantification method in comparison with other means, thus we believe that the binding constant is likely in the order of magnitude of 10 4 M −1 .…”
Section: Binding Parameters Determinationmentioning
confidence: 98%
See 3 more Smart Citations
“…It was reported that the solubility of protonated CFZ under acidic conditions is 20 mg L −1 . 25 The phase solubility data based on the HPLC-UV method and 1 H NMR titration method afforded the binding constant K a of 2.66 (±0.13) × 10 4 M −1 and 3.15 (±0.16) × 10 5 M −1 , respectively. HPLC analysis is often considered as a more accurate quantification method in comparison with other means, thus we believe that the binding constant is likely in the order of magnitude of 10 4 M −1 .…”
Section: Binding Parameters Determinationmentioning
confidence: 98%
“…The improved solubility of CFZ was likely due to amine protonation under acidic conditions. 10,25,60 In the presence of CB [7] under both neutral and acidic conditions, the color of the solutions deepened significantly, which was mainly attributed to the dissolution of CFZ when complexed with CB [7] (Fig. 1).…”
Section: H Nmr Titration Of the Host-guest Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have been reported almost exclusively focus on enhancing the solubility of hydrophobic drugs. [23,24] …”
mentioning
confidence: 99%